ANALISIS ANALISIS KARAKTER TOKOH DALAM KARYA SASTRA LAMA PAN BALANG TAMAK - Ardita, Wayan; I Nengah Sueca (Universitas Swadaya Gunung Jati, 2025)
Indonesian old literature, as a rich cultural heritage, reflects the values of life upheld by various societal strata and eras, with the story of Pan Balang Tamak serving as a significant example. This study aims to describe the character of Pan Balang Tamak and explore the moral values embedded in the narrative, including cleverness, wisdom, and critique of social injustice. The qualitative research method employed involves a descriptive analysis of the literary text, with a focus on character development and interactions within the cultural context of Bali. The findings reveal that the character of Pan Balang Tamak not only illustrates the complexity of human nature but also conveys relevant moral messages, such as the importance of critical thinking and resistance to injustice. This character inspires younger generations to understand and challenge unjust social norms, while also imparting values of wisdom and creativity essential for navigating the challenges of the modern era. Thus, this study affirms the importance of preserving classical literature as an educational medium capable of shaping societal character and safeguarding cultural heritage.